2019
DOI: 10.1007/s11665-019-04399-z
|View full text |Cite
|
Sign up to set email alerts
|

The Condition of Ni-Cr Alloy Surface After Abrasive Blasting with Various Parameters

Abstract: The parameters of abrasive blasting process directly affect the condition of the metal surface, changing the degree of surface roughness and wettability, depending on the size of the used particle, the pressure or type of abrasive. The aim of this study was to analyze the condition of Ni-Cr alloy surface after abrasive blasting using various process variants. The samples were blasted by Al 2 O 3 abrasive using various particle sizes and pressures of the process. Basic and specific roughness parameters were inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…Similar results were obtained in zirconium oxide [18] and titanium [19] research. By comparing the results obtained in this study with the results from [20]-where the same nickel-chromium alloy was used, but aluminum oxide was the abrasive-it can be observed that the influence of the processing parameters on the surface condition changes as a result of both the pressure and the abrasive size. However, the values of measured parameters are higher after the processing using silicon carbide.…”
Section: Discussionmentioning
confidence: 80%
“…Similar results were obtained in zirconium oxide [18] and titanium [19] research. By comparing the results obtained in this study with the results from [20]-where the same nickel-chromium alloy was used, but aluminum oxide was the abrasive-it can be observed that the influence of the processing parameters on the surface condition changes as a result of both the pressure and the abrasive size. However, the values of measured parameters are higher after the processing using silicon carbide.…”
Section: Discussionmentioning
confidence: 80%
“…It is related to the change of the material surface condition in relation to the subjected only to milling. The treatment parameters also affect the treated surface condition [ 15 ], e.g., its roughness and surface free energy.…”
Section: Discussionmentioning
confidence: 99%
“…One of these factors may be the amount of embedded abrasive in the metal surface. Research has shown that different amounts of abrasive material are embedded in treated surfaces [ 15 , 21 , 22 ]. It is not easy to define this impact clearly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SFE calculations were made by dividing into the dispersion (apolar) component, the polar component, and the total surface energy. The Owens–Wendt model was used to calculate the values of individual dispersion and the polar components of the tested samples [ 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%